Accelerating lipid production in freshwater alga Chlorella sorokiniana SDEC-18 by seawater and ultrasound during the stationary phase. (December 2020) - Xie, Zhen; Pei, Haiyan; Zhang, Lijie; Yang, Zhigang; Nie, Changliang; Hou, Qingjie; Yu, Ze
Abstract: Seawater integrated with ultrasound treatment was applied to cultivate freshwater microalgae for improving both cell density and lipid content in two-stage method. In this study, Chlorella sorokiniana SDEC-18 was cultured in seawater through two stages, which comprised fast cell growth in stage I, followed by lipid stimulation in stage II to improve lipid productivity. Seawater and ultrasound, applied in stage II, improved microalgae growth greatly by removing 19% of the algal extracellular substances (AESs), and further increased the lipid accumulation from 50.53% to 64.38% in seawater. Hence, after 6 days of stage II, lipid productivity value of 28.78 mg/L/d was obtained, which was about 3.2 times more than that in the BG11 (Blue-Green Medium) control. These results prove that uniting seawater and ultrasound paves the way towards higher lipid productivity of freshwater microalgae. Graphical abstract: Image 1 Highlights: Seawater promoted lipid accumulation in freshwater algae at the cost of biomass. Seawater coupled by ultrasound helped microalgal lipid content reach up to 64%. Ultrasonication in seawater improved algal growth greatly by degrading the AESs. Lipid productivity of 28.78 mg/L·d was obtained, trebling the value of the BG11.